2017
DOI: 10.1021/acs.joc.7b00405
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Transformations Using Molecular Oxygen-Doped Carbon Materials

Abstract: Carbon materials like activated carbon (AC) undergo chemisorption with O to give species with electron deficiency in the carbon skeleton and negative charge at the oxygen end that upon reaction with PPh and benzoic acid afford PhP═O. Whereas amine donors react with O-chemisorbed AC and nucleophiles to give dehydrogenatively coupled products in 67-89% yields via the corresponding radical cation and iminium ion intermediates, the reactions using β-naphthoxide derivatives give the corresponding oxidatively couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Also GO gave a relatively poor yield (entry 10). The related oxidation ability of AC has been previously associated to absorbed oxygen in AC that enables some stoichiometric activity in ODH couplings . The HCl‐treated CNTs provide a poor yield of 27 % (entry 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also GO gave a relatively poor yield (entry 10). The related oxidation ability of AC has been previously associated to absorbed oxygen in AC that enables some stoichiometric activity in ODH couplings . The HCl‐treated CNTs provide a poor yield of 27 % (entry 6).…”
Section: Methodsmentioning
confidence: 99%
“…The related oxidation ability of AC hasb een previously associated to absorbed oxygen in AC that enables some stoichiometric activity in ODH couplings. [32] The HCltreated CNTsp rovide ap oor yield of 27 %( entry 6). It hasb een shown that this treatmentl owers overall oxygen contento f MWCNTs.…”
mentioning
confidence: 99%
“…Proposed mechanism of polyaniline functionalization. When graphitic sh-scale carbon is heated at 250 C in O 2 atmosphere, 42,43 charged oxygen species on carbon surface are formed as shown in Fig. 10.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…Recently, we reported that the oxygen adsorbed carbon materials 3 react with Ph 3 P and benzoic acid to give Ph 3 PO exploiting the peroxy moiety and react with the electron donors like N‐phenyl tetrahydroisoquinoline and 2‐naphthol resulting in some useful transformations involving electron transfer from these donors to the electron deficient carbon skeleton via the intermediacy of the corresponding radical intermediates (Scheme ) . In continuation of these efforts, we wish to report herein that the oxygen adsorbed carbon materials like activated carbon (AC) and carbon black (CB) are useful for the oxidation of organoboranes and for the preparation of Ph 3 P:BH 3 and pyridine:BH 3 complexes by reaction with NaBH 4 and Ph 3 P or pyridine.…”
Section: Introductionmentioning
confidence: 99%